Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/0161734619882683
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Diagnosis of Breast Nodules Using Modified Faster R-CNN

Abstract: Breast cancer has become the biggest threat to female health. Ultrasonic diagnosis of breast cancer based on artificial intelligence is basically a classification of benign and malignant tumors, which does not meet clinical demand. Besides, the current target detection method performs poorly in detecting small lesions, while it is clinically required to detect nodules below 2 mm. The objective of this study is to (a) propose a diagnostic method based on Breast Imaging Reporting and Data System (BI-RADS) and (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Further, Yolo V3 employs the sigmoid function as a tool for predicting the activation function. The sigmoid function solves the problem efficiently, while the equal target has two labels [39,41,42].…”
Section: Traffic Sign Recognition With You Only Look Once (Yolo) V3mentioning
confidence: 99%
“…Further, Yolo V3 employs the sigmoid function as a tool for predicting the activation function. The sigmoid function solves the problem efficiently, while the equal target has two labels [39,41,42].…”
Section: Traffic Sign Recognition With You Only Look Once (Yolo) V3mentioning
confidence: 99%
“…An AI-based colonoscopy system has been shown to accurately differentiate neoplastic lesions from nonneoplastic lesions on stained endocytoscopic images and endocytoscopic narrow-band images in endoscopic evaluation of small colon polyps (7). The application of AI for US-based diagnosis has been mainly reported for the diagnosis of malignant tumors, such as mammary and thyroid cancers (8)(9)(10)(11). Le et al reported an AI model for the diagnosis of thyroid cancer pre-trained with 312,399 B-mode US images of cancer and healthy controls (12).…”
Section: History and Recent Progress Of Ai In Medical Imagingmentioning
confidence: 99%
“…Since the initial release of the BI-RADS lexicon for ultrasound (BI-RADS-US) in 2003 [ 4 ], together with the rapid development of technique, ultrasound is getting more used for breast screening, especially in Asian women with dense breasts [ 5 ]. Compare to mammography, ultrasound examination is a portable, real-time, non-invasive, non-radiative, inexpensive, and highly reproducible method, and well accepted by patients [ 5 7 ]. BI-RADS-US is confirmed to be feasible to offer typical features for benign or malignant breast lesions [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%